S-nitrosothiols, and other products of nitrate metabolism, are increased in multiple human blood compartments following ingestion of beetroot juice - Mohammed Abu-Alghayth (Redox Biology, 2021)
Ingested inorganic nitrate (NO3⁻) has multiple effects in the human body including vasodilation, inhibition of platelet aggregation, and improved skeletal muscle function. The functional effects of oral NO3⁻ involve the in vivo reduction of NO3⁻ to nitrite (NO2⁻) and thence to nitric oxide (NO). However, the potential involvement of S-nitrosothiol (RSNO) formation is unclear. We hypothesised that the RSNO concentration ([RSNO]) in red blood cells (RBCs) and plasma is increased by NO3⁻-rich beetroot juice ingestion. In healthy human volunteers, we tested the effect of dietary supplementation with NO3⁻-rich beetroot juice (BR) or NO3⁻-depleted beetroot juice (placebo; PL) on [RSNO], [NO3⁻] and [NO2⁻] in RBCs, whole blood and plasma, as measured by ozone-based chemiluminescence. The median basal [RSNO] in plasma samples (n = 22) was 10 (5–13) nM (interquartile range in brackets). In comparison, the median values for basal [RSNO] in the corresponding RBC preparations (n = 19) and whole blood samples (n = 19) were higher (p < 0.001) than in plasma, being 40 (30–60) nM and 35 (25–80) nM, respectively. The median RBC [RSNO] in a separate cohort of healthy subjects (n = 5) was increased to 110 (93–125) nM after ingesting BR (12.8 mmol NO3⁻) compared to a corresponding baseline value of 25 (21–31) nM (Mann-Whitney test, p < 0.01). The median plasma [RSNO] in another cohort of healthy subjects (n = 14) was increased almost ten-fold to 104 (58–151) nM after BR supplementation (7 × 6.4 mmol of NO3⁻ over two days, p < 0.01) compared to PL. In conclusion, RBC and plasma [RSNO] are increased by BR ingestion. In addition to NO2⁻, RSNO may be involved in dietary NO3⁻ metabolism/actions.